The Relationship of Parenting to Children's Cognitive Development - Rahmawati, Apriana; Nurbaiti, Nurbaiti; Wardani, Nuniek Setyo; Wulandari, Shenda Maulina (Jurnal Surya, 2022)
Introduction: Parenting is an important aspect of the growth and development of children because parents are the first place for children to grow and develop. Deficiencies in one aspect of the development will affect the subsequent development of children into adulthood. The purpose of the study was to analyze the relationship between parenting and cognitive development of elementary school children in grade 1 at Madrasah Ibtidaiyah Iaanatul Ikhwan, Depok.Methods: The research method was descriptive quantitative with a cross-sectional approach with 20 participants. The result of this study is data about cognitive development in age-school childrenResults: The results of the research on the cognitive development of children are the majority of good cognitive development (65 %), sufficient cognitive development (25 %), and less cognitive development (10 %). The results of the chi-square statistical test obtained the Pearson chi-square value with a p-value of 0.007.Conclusion: There is a relationship between parenting and the cognitive development of children. This is an important note for parents to provide good care to their children.